Territórios e sentidos: espaço, cultura, subjetividade e cuidado na atenção psicossocial - Lima, Elizabeth Maria Freire De Araújo [UNESP]; Yasui, Silvio (Centro Brasileiro de Estudos de Saúde, 2014)
In the light of the collective health and of the mental health, the concept of territory is present in multiple dimensions and meanings. It appears in documents that express principles and guidelines of the health policies and in the planning of local actions, and it is a central element to organize the care network in psychosocial attentiveness. This present essay aims to discuss the concept of territory and its uses in the practices of psychosocial care, developing a dialogue with the geographer Milton Santos and the philosophers Gilles Deleuze and Félix Guattari who, from different fields and perspectives, work with this concept. This dialogue made it possible to think the territory in its complexity, as space, process and composition, in order to optimize the relationship between service, culture, production of care and production of subjectivity.

No contexto da saúde coletiva e da saúde mental, o conceito de território está presente em múltiplas dimensões e sentidos. Aparece em documentos que expressam princípios e diretrizes das políticas de saúde e no planejamento das ações locais, e é elemento central para organizar a rede de cuidado na atenção psicossocial. O presente ensaio busca discutir o conceito de território e seus usos nas práticas da atenção psicossocial, desenvolvendo um diálogo com o geógrafo Milton Santos e os filósofos Gilles Deleuze e Félix Guattari, que, de campos e perspectivas distintas, trabalham com esse conceito. Este diálogo possibilitou pensar o território em sua complexidade, como espaço, processo e composição, de forma a potencializar a relação entre serviço, cultura, produção do cuidado e produção de subjetividade.
Territories and meanings: space, culture, subjectivity and care in psychosocial attentiveness
Keywords: Mental health services; Public health; Culture; Serviços de saúde mental; Saúde pública; Cultura